Discussing Ficus carica as a Natural and Blessed Antioxidant, a Medical Literature Review Study Based on a Qur'anic Verse and a Hadith Report - Amiruddin, Muhammad; Fatimah, Dewi; Wulandari, Luky Putri (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
This fruit is not an ordinary fruit. Its scientific name is Ficus carica. More are spread in subtropical and tropical areas around the world. In the last Heavenly scripture, one of these particular species of Ficus is given a special oath equivalent to God's special oath to the sun. The Closing Word of Prophethood is believed by the bearer of blessings. This article discusses the strengths and privileges of the Ficus Carica plant content in a health science review through its amazing natural antioxidants. This article conducts a systematic analysis and synthesizes the findings of existing research related to the antioxidant content of the Ficus Carica. The result tells, Ficus Carica rich in antioxidants and fiber that play a role in helping protect the body's cells from free radicals that can cause inflammation and cell damage and prevent cardiovascular disease, diabetes mellitus, and cancer. Compounds such as triterpenoids and flavonoids in figs are similar to insulin that prevent diabetes mellitus. In Islam, the choice of figs as a medical ingredient is not just a natural factor, but a factor that he is blessed with by Allah Subhanahu Wa Ta'ala.